Is chemically reactive membrane crystallisation faciliated by heterogeneous primary nucleation? Comparison with conventional gas-liquid crystallisation for ammonium bicarbonate precipitation in a CO2-NH3-H2O system - Bavarella, Salvatore; Hermassi, Mehrez; Brookes, Adam; Moore, Andrew; Vale, Peter C. J.; Di Profio, Gianluca; Curcio, Efrem; Hart, Phil; Pidou, Marc; McAdam, Ewan (American Chemical Society, 2020)
In this study, membrane crystallisation is compared to conventional gas-liquid crystallisation for the precipitation of ammonium bicarbonate, to demonstrate the distinction in kinetic trajectory and illustrate the inherent advantage of phase separation introduced by the membrane to crystallising in gas-liquid systems. Through complete mixing of gas and liquid phases in conventional crystallisation, high particle numbers were confirmed at low levels of supersaturation. This was best described by secondary nucleation effects in analogy to mixed suspension mixed product removal (MSMPR) crystallisation, for which a decline in population density was observed with an increase in crystal size. In contrast, for membrane crystallisation, fewer nuclei were produced at an equivalent level of supersaturation. This supported growth of fewer, larger crystals which is preferred to simplify product recovery and limit occlusions. Whilst continued crystal growth was identified with the membrane, this was accompanied by an increase in nucleation rate which would indicate the segregation of heterogeneous primary nucleation from crystal growth, and was confirmed by experimental derivation of the interfacial energy for ammonium bicarbonate (σ, 6.6 mJ m-2), which is in agreement to that estimated for inorganic salts. The distinction in kinetic trajectory can be ascribed to the unique phase separation provided by the membrane which promotes a counter diffusional chemical reaction to develop, introducing a region of concentration adjacent to the membrane. The membrane also lowers the activation energy required to initiate nucleation in an unseeded solution. In conventional crystallisation, the high nucleation rate was due to the higher probability for collision, and the gas stripping of ammonia (around 40% loss) through direct contact between phases which lowered pH and increased bicarbonate availability for the earlier onset of nucleation. It is this high nucleation rate which has restricted the implementation of gas-liquid crystallisation in direct contact packed columns for carbon capture and storage. Importantly, this study evidences the significance of the membrane to governing crystallisation for gas-liquid chemical reactions through providing controlled phase separation.
Keywords: nucleation; crystal growth; chemical absorption; carbon dioxide; ammonia